A job guarantee for Austria’s long term unemployed - Picek, Oliver (Momentum Quarterly, 2020)
Government programmes featuring direct employment of the long-term unemployed have recently resurfaced as part of the economic policy agenda in several European countries. By design, they have not targeted all unemployed people who need a (publicly subsidised) job due to their limited size. For Austria, I propose a comprehensive job guarantee for the long-term unemployed. Every long-term unemployed citizen shall receive an offer for a guaranteed state-funded job in the wider public or NGO sector. An extremely high uptake rate among eligible persons would require 150,000 additional jobs, which would cost between 0.68 and 1.34 billion euros depending on the precise gross salary paid in Job Guarantee employment. This corresponds to 0.19-0.36 percent of Austrian gross domestic product in 2017.
Keywords: Long-term unemployment; Aktion 20.000; Right to work; Job guarantee; Work guarantee; Employer of last resort; ELR; Buffer stock employment